2007
DOI: 10.1016/j.eplepsyres.2007.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Rats bred for susceptibility to depression-like phenotypes have higher kainic acid-induced seizure mortality than their depression-resistant counterparts

Abstract: Epidemiological evidence suggests that epilepsy and depression are comorbid diseases. In fact, depression is the most common neuropsychiatric disorder associated with epilepsy, particularly temporal lobe epilepsy, and individuals with a history of depression are at a higher risk for developing epilepsy than the general population. Despite the epidemiological evidence for this link, there has been little experimental evidence to support the connection or elucidate possible underlying mechanisms. In an effort to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…Importantly, when SwLo rats were given an antidepressant, chronic but not acute administration increased their swim test activity (West and Weiss, 1998a). Information on neurotransmitter involvement was limited, but studies suggest involvement of both glutamatergic (Tabb et al, 2007) and dopaminergic (West et al, 1999a;West et al, 1999b) mechanisms as well as alterations of the stress axis (Gutman et al, 2008). Since dysfunctions (hyper-or hypoactivity) of the hypothalamic-pituitary-adrenal axis may play a prominent role in the development of major depressive disorders (Bale, 2006;De Kloet et al, 1998;Holsboer, 2000), researchers have attempted to generate animal models that mimic these neuroendocrine core symptoms with the goal of unraveling the parameters underlying increased or decreased stress reactivity (Touma et al, 2008).…”
Section: Validity Of Fsl Model Including Comparison With Other Animamentioning
confidence: 99%
“…Importantly, when SwLo rats were given an antidepressant, chronic but not acute administration increased their swim test activity (West and Weiss, 1998a). Information on neurotransmitter involvement was limited, but studies suggest involvement of both glutamatergic (Tabb et al, 2007) and dopaminergic (West et al, 1999a;West et al, 1999b) mechanisms as well as alterations of the stress axis (Gutman et al, 2008). Since dysfunctions (hyper-or hypoactivity) of the hypothalamic-pituitary-adrenal axis may play a prominent role in the development of major depressive disorders (Bale, 2006;De Kloet et al, 1998;Holsboer, 2000), researchers have attempted to generate animal models that mimic these neuroendocrine core symptoms with the goal of unraveling the parameters underlying increased or decreased stress reactivity (Touma et al, 2008).…”
Section: Validity Of Fsl Model Including Comparison With Other Animamentioning
confidence: 99%
“…Although the focus of this study was on the SwLo rats as a model for susceptibility to epilepsy and depression, the SwHi rats are also of interest. Because the depression-and epilepsy-like phenotypes of 'wild-type', non-selected rats tend to fall somewhere in between those of SwLo and SwHi rats (Tabb et al, 2007;Weiss et al, 1998;Weiss et al, 2008;unpublished data), the SwHi rats may be a model for co-morbidity resilience.…”
Section: Resultsmentioning
confidence: 99%
“…In that paper, we reported that SwLo rats have increased mortality following kainic acid-induced limbic seizures, but no differences in flurothyl-induced generalized seizure susceptibility, suggesting that the SwLo rats are specifically sensitive to limbic seizures (Tabb et al, 2007). This was of particular interest because the rate of depression is higher for patients with temporal lobe epilepsy, who suffer from recurrent limbic seizures, than other forms of epilepsy (Kondziella et al, 2007;Piazzini et al, 2001).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Π’ большом исслСдовании, ΠΏΡ€ΠΎΠ²Π΅Π΄Π΅Π½Π½ΠΎΠΌ Π½Π° крысах, Π²Ρ‹Π²Π΅Π΄Π΅Π½Π½Ρ‹Ρ… Π½Π° Ρ‡ΡƒΠ²ΡΡ‚Π²ΠΈΡ‚Π΅Π»ΡŒΠ½ΠΎΡΡ‚ΡŒ (Π»ΠΈΠ½ΠΈΠΈ SwLo, SUS, HYPER) ΠΈΠ»ΠΈ Ρ€Π΅Π·ΠΈΡΡ‚Π΅Π½Ρ‚Π½ΠΎΡΡ‚ΡŒ (Π»ΠΈΠ½ΠΈΠΈ SwHi, RES, MON RES) ΠΊ дСпрСссивноподобным Ρ„Π΅Π½ΠΎΡ‚ΠΈΠΏΠ°ΠΌ, ΠΏΠΎΠΊΠ°Π·Π°Π½ΠΎ, Ρ‡Ρ‚ΠΎ пСрвая Π³Ρ€ΡƒΠΏΠΏΠ° Π»ΠΈΠ½ΠΈΠΉ дСмонстрируСт Π±ΠΎΠ»Π΅Π΅ Π²Ρ‹ΡΠΎΠΊΡƒΡŽ ΡΠΌΠ΅Ρ€Ρ‚Π½ΠΎΡΡ‚ΡŒ послС судороТной активности, Π²Ρ‹Π·Π²Π°Π½Π½ΠΎΠΉ ΠΊΠ°-ΠΈΠ½ΠΎΠ²ΠΎΠΉ кислотой, Π² сравнСнии со Π²Ρ‚ΠΎΡ€ΠΎΠΉ, рСзистСнтной [33]. ΠšΡ€Ρ‹ΡΡ‹ Π»ΠΈΠ½ΠΈΠΈ SwLo, сСлСктивно ΠΎΡ‚ΠΎΠ±Ρ€Π°Π½Π½Ρ‹Π΅ Π½Π° Π΄Π΅-прСссивноподобноС ΠΏΠΎΠ²Π΅Π΄Π΅Π½ΠΈΠ΅, Ρ…Π°Ρ€Π°ΠΊΡ‚Π΅Ρ€ΠΈΠ·ΡƒΡŽΡ‚ΡΡ ΠΏΠΎΠ²Ρ‹-шСнной Ρ‡ΡƒΠ²ΡΡ‚Π²ΠΈΡ‚Π΅Π»ΡŒΠ½ΠΎΡΡ‚ΡŒΡŽ ΠΊ лимбичСским судорогам, ΠΏΡ€ΠΈ этом усилСнная физичСская Π°ΠΊΡ‚ΠΈΠ²Π½ΠΎΡΡ‚ΡŒ сниТаСт ΠΊΠ°ΠΊ проявлСния дСпрСссии, Ρ‚Π°ΠΊ ΠΈ ΠΊΠΎΠ½Π²ΡƒΠ»ΡŒΡΠΈΠ²Π½ΡƒΡŽ Π°ΠΊΡ‚ΠΈΠ²Π½ΠΎΡΡ‚ΡŒ Π² ΠΎΡ‚Π²Π΅Ρ‚ Π½Π° Π²Π²Π΅Π΄Π΅Π½ΠΈΠ΅ ΠΏΠΈΠ»ΠΎΠΊΠ°Ρ€ΠΏΠΈΠ½Π° [34].…”
unclassified